Lifestyle-related behaviour modifications during examinations in undergraduate medical students in India - Kilaru, Tanuja; Pradhan, Divyang; Yadav, Deepika; M., Shwethashree; Doddaiah, Sunil Kumar (International Journal Of Community Medicine And Public Health, 2024)
Background: Examinations are formal tests conducted to assess a student’s knowledge. Despite their paramount importance, they can impact students physically and mentally by causing stress and anxiety. Hence, identifying the changes that hamper a student’s lifestyle, during examinations, in order to prevent the development of unhealthy behavioral patterns is the goal of this study. Methods: It was a cross-sectional study conducted among undergraduate medical students of Mysuru over a period of 2 months from February 2023 to April 2023 in 120 participants. Data was collected using an online questionnaire, entered into M.S. Excel and analyzed using SPSS software. Frequencies and percentages were calculated for all the categorical variables. Results: 61.7% of the study participants showed extreme examination stress. Only 39.3% consumed 3 balanced meals daily. A complete lack of physical activity was observed in 38.1%. Regular caffeine consumption was noted in 46.4% and 27.4% showed unusual amounts of junk food daily. Irregular sleeping patterns were found in 23.8%, sleeping at odd times beyond 1 am was noted in 59.5% and deficient sleep duration (<6 hours) was observed in 46.6% of the surveyed population. Conclusions: The findings from this survey highlight the significant impact of examinations on the lifestyle-related behaviors of undergraduate students such as high prevalence of extreme examination stress, irregular eating habits, lack of physical activity, and sleep deprivation.